The constitution of the teaching identity from the PPCs of the Geography courses degree in the Southern region of Brazil (PerCursos, 2022)
This article is an excerpt of a master's research whose central theme was the analysis of the conceptions and constitutions of teaching identities identified in the PPCs of the Geography Licentiate courses. It aims to analyze the construction of teaching identity from the PPCs of Undergraduate Geography courses in the southern region of Brazil. The methodology is based on Discursive Textual Analysis (DTA), which seeks to read the analyzed data by moving between the two forms: content analysis and discourse analysis, being the key to the study of PPCs, specifically the objectives of the courses and from the professional profiles of each university selected for the research, UEM, UDESC and FURG. From the analysis of specific fragments of the PPCs, such as the objectives of the courses and their professional profiles, it was possible to perceive that each university proposes a different professional profile to the future teacher, in addition to the fact that the objectives of the course deal with different issues, even though, all, Undergraduate Geography courses. With the visualization of the categories, both initial, intermediate and final, that emerged from the speeches of the PPCs that it was proposed to analyze, it was possible to perceive new dialogues and conversations between the conceptions that the degree courses in Geography aim for their students. It is essential that the pedagogical projects of the courses have clear what they expect from the training of students and that the proposition of the objectives - general and specific - are aligned with the professional profiles that they hope to produce, constituting professionals capable of acting as Geography teachers.
Keywords: identity and teaching knowledge; teacher training; curriculum; pedagogical political project